Pregnancy after Obstetric Fistula: Should It Be Encouraged? - Shrestha, Ranjana; Tiwari, Kenusha Devi; Dangal, Ganesh; Karki, Aruna; Pradhan, Hema; Bhattachan, Kabin; Poudel, Rekha; Bajracharya, Nishma; Bharati, Sonu (Nepal Journal of Obstetrics and Gynaecology, 2018)
Obstetric fistula (OF) is a life-changing morbidity associated with childbirth. It occurs especially after a prolonged obstructed labor and is a major public health problem in the developing countries. The smell of stool and urine leads to the ostracization and rejection of fistula patients by their spouses, families, friends and society in whole. Surgical treatment of fistula is possible. However, this successful outcome of fistula repair surgery is dependent on pre-operative care and the post-operative care such as delaying the commencement of sexual intercourse and delaying conception. Family planning can aid to this. Pregnancy is advised after minimum of 12 months’ post-repair and mode of delivery should be elective cesarean section. Here, we present a case of 23 years’ female, who suffered from obstetric fistula who underwent obstetric fistula repair twice, re-married and conceived after a year with successful elective cesarean delivery.